2019
DOI: 10.26508/lsa.201800283
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the repertoire of glucocorticoid receptor target genes by engineering genomic response elements

Abstract: The glucocorticoid receptor (GR), a hormone-activated transcription factor, binds to a myriad of genomic binding sites yet seems to regulate a much smaller number of genes. Genome-wide analysis of GR binding and gene regulation has shown that the likelihood of GR-dependent regulation increases with decreased distance of its binding to the transcriptional start site of a gene. To test if we can adopt this knowledge to expand the repertoire of GR target genes, we used CRISPR/Cas-mediated homology-directed repair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(85 reference statements)
0
9
0
Order By: Relevance
“…ATAC-seq data for GR (1 μM Dex, 1.5 h or 0.1% EtOH as vehicle control) is from a previous study ( 30 ), ArrayExpress accession number E-MTAB-7746. For AR (5 nM R1881 or 0.1% dmso as a vehicle control, 4 h), ATAC-seq was done as described ( 30 ). ArrayExpress accession number for ATAC-seq data: E-MTAB-9606.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATAC-seq data for GR (1 μM Dex, 1.5 h or 0.1% EtOH as vehicle control) is from a previous study ( 30 ), ArrayExpress accession number E-MTAB-7746. For AR (5 nM R1881 or 0.1% dmso as a vehicle control, 4 h), ATAC-seq was done as described ( 30 ). ArrayExpress accession number for ATAC-seq data: E-MTAB-9606.…”
Section: Methodsmentioning
confidence: 99%
“…Processing of ATAC-seq data was done as previously described in ( 30 ), with the addition that reads of mapping quality <10 were filtered out using SAMtools v1.10 ( 40 ). BigWig tracks for genome browser visualization were generated with bamCoverage (options: –normalizeUsing RPKM; –binSize 20; –smoothLength 60) from deepTools v3.4.1 ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…X-ray crystallography of GR DBD dimers bound to different GBSs showed that conformation of the lever arm in the DBD appeared to be influenced by the DNA sequence (24, 119). Furthermore, the addition of a single GR-binding site was sufficient to convert a gene, which was normally not regulated by GR, into a target gene, such as IL-1 β and IL1R2 in U2OS cells (120). The presence of classical GREs in GR-bound enhancers near both activated and repressed genes in murine bone marrow-derived macrophages (BMDM) stimulated with LPS and Dexamethasone (Dex) challenge these models.…”
Section: Introductionmentioning
confidence: 99%
“…Because GRs function within complexes, GR binding to a GRE, on its own, is not a strong predictor of GR-dependent gene regulation. The likelihood of an occupied GRE driving transcriptional regulation of a gene increases the closer that the GRE is to the gene’s transcriptional start site [ 13, 14 ]. GR binding sites can also work concordantly, with clusters of GREs mediating GR-dependent transcription [ 14 ].…”
Section: Glucocorticoid Steroids Act Through the Glucocorticoid Recepmentioning
confidence: 99%